TINJAUAN TERHADAP DOKTRIN KOVENAN KERJA DALAM TEOLOGI REFORMED - Ranjawali Matalu (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2014)
In this article, the writer deals with the origin of covenant of works doctrine which, according to the writer, was started at the Reformation era. The writer believes that this doctrine is originated by Bullinger and Calvin. However, in its development, there are dissenting views within Reformed Theologians on whether the covenant of works doctrine is taught in the scripture. Therefore, the writer then analyzes the arguments given by those who disagree with the doctrine of covenant of works. From the analysis, the writer concludes that their given arguments are not in line with the teaching of the scripture. This conclusion brought us to see the further doctrinal implication that entails when we receive the doctrine of covenant of works. In this article, the writer deals with two doctrinal implications, the transmission of sin and the sinlessness of Christ.